2016
DOI: 10.3904/kjim.2014.373
|View full text |Cite|
|
Sign up to set email alerts
|

Two-year clinical outcomes in stable angina and acute coronary syndrome after percutaneous coronary intervention of left main coronary artery disease

Abstract: Background/AimsThis study appraised the long term clinical outcomes of patients treated with percutaneous coronary intervention (PCI) for unprotected left main coronary artery (ULMCA) disease. There are limited data regarding long-term clinical outcomes after PCI for ULMCA disease.MethodsFrom 2001 to 2011, a total of 448 patients who underwent PCI for ULMCA disease and had 2-year clinical follow-up, were analyzed. The study patients were divided into two groups: group I (stable angina pectoris [SAP], n = 60, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In the present study, ACS was associated with long‐term mortality and more comorbid illnesses, but once these differences were adjusted for, ACS did not independently confer elevated mortality risk. This finding is in line with previous studies 11,12 . Chronic kidney disease stage ≥ 3, high EuroSCORE II, and laser atherectomy use were independents predictors of long‐term mortality, with the latter probably reflecting the complexity of CAD, as the laser is usually reserved for resistant severely calcified and uncrossable lesions and/or calcified resistant instant restenosis 13 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, ACS was associated with long‐term mortality and more comorbid illnesses, but once these differences were adjusted for, ACS did not independently confer elevated mortality risk. This finding is in line with previous studies 11,12 . Chronic kidney disease stage ≥ 3, high EuroSCORE II, and laser atherectomy use were independents predictors of long‐term mortality, with the latter probably reflecting the complexity of CAD, as the laser is usually reserved for resistant severely calcified and uncrossable lesions and/or calcified resistant instant restenosis 13 …”
Section: Discussionsupporting
confidence: 88%
“…This finding is in line with previous studies. 11,12 Chronic kidney disease stage ≥ 3, high Euro-SCORE II, and laser atherectomy use were independents predictors of long-term mortality, with the latter probably reflecting the complexity of CAD, as the laser is usually reserved for resistant severely calcified and uncrossable lesions and/or calcified resistant instant restenosis. 13 The SYNTAX score is an angiographic tool used to grade the complexity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…We have found patients with HTA to be at more than 3 times higher risk of suffering from cardiovascular symptoms during the follow-up period after AMI. In the previous studies, somewhat lower hazard risk ratio was found for these patients to experience major adverse cardiovascular events [22,23], but it may rise to 5 times higher risk in patients with unspecified chest pain [24]. Therefore, patients on antihypertensive drugs, such as calcium channel blockers, were associated with worse prognosis, as well.…”
Section: Discussionmentioning
confidence: 93%
“…Management of acute coronary syndrome (ACS) including ST-segment elevation myocardial infarction (STEMI) and non-STEMI, [ 6 ] and also several types of nonsevere multivessel coronary artery diseases (MVCADs), [ 7 ] and unprotected left main coronary artery diseases (ULMCAD) is nowadays possible with PCI. [ 8 ] Even though PCI might be an acceptable choice in most of the patients, certain patients’ conditions and the extent of coronary lesions might restrict its use, thereby shifting its place to coronary artery bypass surgery (CABG). [ 9 ]…”
Section: Introductionmentioning
confidence: 99%